The Influence of Service Quality and Employee Loyalty on Customer Satisfaction in Credit Realization in 2023 at PT. Bank Tabungan Negara (Persero) Tbk. KCP Negara - Dwiyanti, Ni Kadek Indah; Clarissa, Sarita Vania; Dwitrayani, Made Christin (Business Management, 2025)
This study aims to analyze the influence of service quality and employee loyalty on customer satisfaction in credit realization at PT. Bank Tabungan Negara (Persero) Tbk. KCP Negara during 2023. The issues raised in this study are based on fluctuations in credit realization and the alleged decline in customer satisfaction despite various improvements in service and human resource management. This study uses a quantitative approach with a survey method through the distribution of questionnaires to 297 respondents selected using probability sampling techniques. Data analysis was performed using multiple linear regression. The results of the study indicate that service quality and employee loyalty simultaneously and partially have a positive and significant effect on customer satisfaction. These findings indicate that improving service quality and employee loyalty can contribute to increased customer satisfaction in the credit realization process. This study is expected to serve as a reference for banks in designing strategies for improving service and employee management.